Analisis Manajemen Persediaan Barang Dagangan Dalam Perspektif Etika Bisnis Islam Pada Medan Mart - Nuryan Hadi; Uswah Hasanah (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study was to determine the implementation of the internal control system for merchandise inventory carried out by Medan Mart and to determine the suitability of marketing management with Islamic business ethics. This research uses a qualitative approach, namely descriptive analysis by carrying out activities in the form of observations, interviews, analyzing those related to merchandise inventory management from the perspective of Islamic business ethics to obtain various kinds of information and then analysing more deeply by the theories that have been obtained previously. Based on the results of the study, it can be concluded that the implementation of internal control of merchandise inventory can play an important role in providing internal control of inventory, providing information about values ??that can support the smooth working process and companies need to provide useful information from errors. In practice, Islamic business ethics in Medan Mart has been going well, with providing service to customers as the main goal